2009
DOI: 10.1177/0170840609349877
|View full text |Cite
|
Sign up to set email alerts
|

Practice as a Members’ Phenomenon

Abstract: Drawing on ethnomethodology and conversation analysis, this article explores the relation between practice and activity; between recruitment practice and the ordinary activities of the job interview. Job interviews are recognizably and accountably different from other interview-formats, such as broadcast news or academic research interviews. Such differences are instantly hearable because ordinary activities are built systematically so as to reveal an orientation to 'practice', distinctive purposes, entitlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The objective of the data collection was the study of the operators' planning practices in allocating resources. We followed Llewellyn and Spence's [32] conceiving practices as members' phenomenon. Therefore, data collection was oriented to the identification of patterns of activities that are intersubjectively organized and recognized by operators as embodying (or not) a certain practice.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of the data collection was the study of the operators' planning practices in allocating resources. We followed Llewellyn and Spence's [32] conceiving practices as members' phenomenon. Therefore, data collection was oriented to the identification of patterns of activities that are intersubjectively organized and recognized by operators as embodying (or not) a certain practice.…”
Section: Methodsmentioning
confidence: 99%
“…plan setup among the operators, following Llewellyn and Spence's (2009) suggestion for conceiving practices as members' phenomenon for the accomplishment of an EM-oriented study of practices. Therefore data collection was not oriented to the mere identification of patterns of activities, but to the study of the details of interactions so as to determine how activities are intersubjectively organised and recognised by operators as embodying (or not) a certain practice.…”
Section: Ilaria Redaelli and Antonella Carassamentioning
confidence: 99%
“…The first stream has generated propositions on when and how moral judgments are possible and desirable (Beadle and Moore, 2006;Holt, 2006;MacIntyre, 1981MacIntyre, [1985; Moore, 2012;Morrell, 2012), engaging with the work of important moral philosophers, such as Aristotle (Morrell and Clark, 2010;Tsoukas, 2004;Tsoukas and Cummings, 1997) and Alasdair MacIntyre. iv The second stream has focused on the equally important and influential work of Harold Garfinkel and ethnomethodology (Fox, 2008;Garfinkel, 1991;Llewellyn and Spence, 2009) to empirically investigate the situated production of social-cum-moral order.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have been a great intellectual inspiration to organizational scholars, who have sought to understand the practical methods through which social and moral order is produced effortfully and on an ongoing basis (Fox, 2008;Llewellyn and Spence, 2009;Suchman, 2000). Fox (2008), for example, argued that, <EXT>from the outset, Garfinkel's "breaching experiments" showed that social order is inseparably moral order and that the organization of interaction is itself morally done.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation